2023
DOI: 10.21203/rs.3.rs-2431862/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise Fabrication of Tactile Sensors using a Custom Additive Manufacturing Platform

Abstract: This paper presents the NeXus, a precision robotic platform with additive manufacturing capabilities that can be used to prototype strain gauge-based tactile sensors – SkinCells - on flexible substrates. An Aerosol Inkjet printer was employed to print the strain gauge structures of the SkinCell sensor. The design of this sensor combines curvilinear geometries representing both a radial shape structure and an arc shape structure, which have opposite gauge responses when the force is applied to the center of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…The results showed a significant reduction in fabrication time and improvements in yield and sensitivity. Other past research reported on the design and fabrication of single tactile strain gauges, using the principles of aerodynamics to precisely align atomized ink droplets on flexible substrates in the NeXus for sensor electrodes [46][47][48][49]. The tactile structures designed and fabricated are ideal for eliminating directional effect due to their circular topology, as characterized in [41,46], but become significantly less effective in a smaller, compact strain gauge size below 6 mm in diameter.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed a significant reduction in fabrication time and improvements in yield and sensitivity. Other past research reported on the design and fabrication of single tactile strain gauges, using the principles of aerodynamics to precisely align atomized ink droplets on flexible substrates in the NeXus for sensor electrodes [46][47][48][49]. The tactile structures designed and fabricated are ideal for eliminating directional effect due to their circular topology, as characterized in [41,46], but become significantly less effective in a smaller, compact strain gauge size below 6 mm in diameter.…”
Section: Contributionsmentioning
confidence: 99%
“…The tactile sensor described in this paper increases the possibility of obtaining a higher spatial resolution due to its small and compact structure, which increases its ability to be condensed in given area when compared to [47]. Finally, to establish a dynamic relationship between the tactile sensory feedback and the indented force measured, we modeled the tactile feedback response data using the system identification framework.…”
Section: Contributionsmentioning
confidence: 99%